2001
DOI: 10.1089/10766290152045039
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Resistance inStreptococcus pyogenesIsolates from Throat Infections in the Region of Aachen, Germany

Abstract: Macrolide-resistance was assessed in 216 consecutive Streptococcus pyogenes isolates from throat infections in the region of Aachen, Germany. Seventeen isolates were resistant to erythromycin: 12 isolates revealed a macrolide (M) phenotype and harbored mefA, and five strains expressed an inducible macrolide-lincosamide-streptogramin B (MLSB) phenotype of which four strains harbored ermA(TR) and one strain contained ermB(AM). Telithromycin (HMR 3647) and quinupristin/dalfopristin remained active particularly ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Prior to the early 1990s, penicillin resistance remained uncommon among clinical isolates of S. pneumoniae in Germany despite the emergence of this problem in many parts of Europe, e.g., Hungary, Spain, and France (2). In contrast, decreased susceptibility to macrolides in S. pyogenes and to ␤-lactams and macrolides in S. pneumoniae has only recently been reported in Germany (4,21,23) and is comparable to resistance rates reported from The Netherlands (10) and Northern European countries (18). Highly penicillin-resistant strains are extremely rare in Germany, as documented by this and other studies.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Prior to the early 1990s, penicillin resistance remained uncommon among clinical isolates of S. pneumoniae in Germany despite the emergence of this problem in many parts of Europe, e.g., Hungary, Spain, and France (2). In contrast, decreased susceptibility to macrolides in S. pyogenes and to ␤-lactams and macrolides in S. pneumoniae has only recently been reported in Germany (4,21,23) and is comparable to resistance rates reported from The Netherlands (10) and Northern European countries (18). Highly penicillin-resistant strains are extremely rare in Germany, as documented by this and other studies.…”
Section: Discussionsupporting
confidence: 82%
“…Brandt et al recently reported macrolide resistance to be present in 17 of 216 (7.9%) S. pyogenes strains isolated from throat infections in the Aachen region of Germany between January 1997 and July 1997 (4). Again, these data suggest that, as for pneumococci, the frequency of macrolide resistance is increasing in Germany.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since we have not encountered emm12.10 elsewhere, it is possible that the population from which we obtained these GAS isolates is relatively segregated. However, except for types emm117, emm33, and emm43 (subtype emm43.4), all of the sequences described in this study have been associated with erythromycin resistance in other countries (2,5,8,15; B. Beall, unpublished data), indicating that the majority of erythromycin-resistant GAS strains could have originated in other countries prior to their introduction into Sofia.…”
mentioning
confidence: 63%
“…We found that macrolide resistance within our sample set of 127 resistant isolates, with the exception of a single erm(B)-positive type emm5.3 isolate, was restricted to sof-positive strains (Table 2) which have been estimated to comprise about 65% of invasive and noninvasive GAS isolates recovered in the United States (B. Beall, unpublished data). Analysis of the published literature concerning macrolide resistance in GAS revealed similar results in Chile, Canada, Finland, Germany, Spain, and Sweden in that each study primarily described macrolide resistance in sof-positive types (including types M2, M4, M11, M12, M22, M28, M58, M73, M75, and M77) (6,12,19,21,27,28,40). (For a compilation of sof PCR-positive types and opacity factor-positive types, see references 4 and 20.)…”
mentioning
confidence: 68%